Про одне перетворення вінерівського процесу в Rm за допомогою функціоналу типу локального часу на поверхні - Осипчук, М.М. (Український математичний журнал, 1993)
The transformation of Wiener's process ξt in ℝm is considered by using the multiplicative functional αt=u(ξt)/u(ξ0), where the function u is similar to a local time type functional on a surface. It is proved that such a transformation is equivalent to a successive application of absolutely continuous change of measure and killing on a surface.